Satisfaction and persistence with vibegron in the first 6 months of overactive bladder treatment: interim results of the phase 4, real-world COMPOSUR study - Roger R. Dmochowski; Eric S. Rovner; Michael J. Kennelly; Diane K. Newman; Keith Xavier; Elizabeth Thomas; Daniel Snyder; Laleh Abedinzadeh (BMC Urology)
Abstract Background The COMPOSUR study is evaluating vibegron for the treatment of overactive bladder (OAB) in a real-world setting. We report results of a prespecified 6-month interim analysis, assessing patient-reported treatment satisfaction, persistence, safety, and tolerability over the first 6 months after receiving a new prescription for vibegron. Methods COMPOSUR (NCT05067478) is a 12-month, phase 4 study of vibegron. Patients were enrolled if they were ≥ 18 years of age with OAB, initiating vibegron after previously receiving anticholinergics (Cohort A) or mirabegron with/without anticholinergics (Cohort B). Satisfaction was assessed via the OAB Satisfaction With Treatment Questionnaire (OAB-SAT-q; domain scores on 0−100 scale, higher scores denoting greater satisfaction). The primary endpoint is the OAB-SAT-q satisfaction domain score. The key secondary endpoints are the percentage of positive responses to OAB-SAT-q questions 1–3 and 11. Additional secondary endpoints include OAB-SAT-q scores for side effects, endorsement, preference, and convenience. Persistence was assessed as an exploratory endpoint. Safety was assessed via adverse events (AEs). Results A total of 403 patients were enrolled and initiated treatment with vibegron; 104 patients discontinued the study before month 6, most commonly owing to withdrawal of consent (n = 32) and AEs (n = 8). Mean (SD) patient age was 56.1 (12.5) years, and 29% were male. Overall, at 6 months, mean (SD) OAB-SAT-q domain scores were 70.0 (21.9) for satisfaction, 84.7 (20.6) for convenience, 91.1 (16.4) for side effects, and 80.4 (20.6) for endorsement. At 6 months, 85.6% (95% CI, 81.1%–90.1%) of patients preferred vibegron to previous OAB treatment. Most patients responded positively to individual OAB-SAT-questions; outcomes were similar from months 1 to 6 and in Cohorts A and B. Persistence with vibegron treatment at 6 months was 73.9% (95% CI, 69.3%–78.0%). Overall, 33.5% of patients experienced a treatment-emergent AE, most commonly (≥ 2% overall) urinary tract infection (4.0%), headache (2.7%), and dizziness (2.2%). Conclusions As of the 6-month interim analysis of the COMPOSUR study, most patients receiving vibegron were satisfied with treatment; satisfaction generally persisted from month 1 to 6, regardless of prior OAB treatment received. Treatment with vibegron was generally safe and well tolerated. Trial registration ClinicalTrials.gov identifier: NCT05067478; registered: October 5, 2021.